A importância do Canvas no planejamento estratégico das Startups: um estudo de caso - Silva, Ângelo Sette da (Universidade do Vale do Rio dos Sinos, 2018)
Startups are innovative companies that have a business model that gains scalability, making their growth exponential. It is believed that most Startups are highly profitable due to the fame of some such as Facebook, Uber, Netflix, etc., but few are known, because most fail. According to a study by Startup Farm, 74% of Startups closed after five years of existence, being 18% before completing two years. Currently most Startups use a tool known as Canvas to develop their business plan, due to its ease, simplicity and way of visualizing all elements of the business model. Despite all its benefits, is Canvas really able to provide all the support needed for Startups to realize their strategic planning? This study sought to understand if the Canvas is enough for the use of the strategic planning in Startups, where was realized interviews with Startups incubated in UNITEC, seeking to understand how their strategic planning is realized. Between the research results highlight the main tools that are used by Startups for the strategic planning. These results contributed to identify if the Canvas is sufficient for the strategic planning to the Startups, besides the creation of a recommendation list to the Startups.
Keywords: Startups; Planejamento estratégico; Canvas; Strategic planning